Immunotherapy Resistance in Glioblastoma - Wang, Elaina J.; Chen, Jia-Shu; Jain, Saket; Morshed, Ramin A.; Haddad, Alexander F.; Gill, Sabraj; Beniwal, Angad S.; Aghi, Manish K. (Frontiers in Genetics, 2021)
Glioblastoma is the most common malignant primary brain tumor in adults. Despite treatment consisting of surgical resection followed by radiotherapy and adjuvant chemotherapy, survival remains poor at a rate of 26.5% at 2 years. Recent successes in using immunotherapies to treat a number of solid and hematologic cancers have led to a growing interest in harnessing the immune system to target glioblastoma. Several studies have examined the efficacy of various immunotherapies, including checkpoint inhibitors, vaccines, adoptive transfer of lymphocytes, and oncolytic virotherapy in both pre-clinical and clinical settings. However, these therapies have yielded mixed results at best when applied to glioblastoma. While the initial failures of immunotherapy were thought to reflect the immunoprivileged environment of the brain, more recent studies have revealed immune escape mechanisms created by the tumor itself and adaptive resistance acquired in response to therapy. Several of these resistance mechanisms hijack key signaling pathways within the immune system to create a protumoral microenvironment. In this review, we discuss immunotherapies that have been trialed in glioblastoma, mechanisms of tumor resistance, and strategies to sensitize these tumors to immunotherapies. Insights gained from the studies summarized here may help pave the way for novel therapies to overcome barriers that have thus far limited the success of immunotherapy in glioblastoma.